The first science result with the JENSA gas-jet target: Confirmation and study of a strong subthreshold F18(p,α)O15 resonance - D.W. Bardayan (Physics Letters B, 2015)
The astrophysical F18(p,α)O15 rate determines, in large part, the extent to which the observable radioisotope 18F is produced in novae. This rate, however, has been extremely uncertain owing to the unknown properties of a strong subthreshold resonance and its possible interference with higher-lying resonances. The new Jet Experiments in Nuclear Structure and Astrophysics (JENSA) gas-jet target has been used for the first time to determine the spin of this important resonance and significantly reduce uncertainties in the F18(p,α)O15 rate.